2020
DOI: 10.1016/j.chemosphere.2019.125594
|View full text |Cite
|
Sign up to set email alerts
|

How can interspecific interactions in freshwater benthic macroinvertebrates modify trace element availability from sediment?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In the sediments, these trace metals become bioavailable, and bioaccumulation of metals in C. bellicosus could be related to the feeding habits of the species, the rates of absorption and depuration, the environmental conditions, the bioavailability of the metals, the fine texture of the sediments, CaCO 3 content, and organic matter content (Jerome and Chukwuka, 2016;Álvaro et al, 2016;Chuan et al, 2017;Genç and Yilmaz, 2017;Çoğun et al, 2017;Annabi et al, 2018;Baki et al, 2018;Durmus et al, 2018;Saber et al, 2018;Hao et al, 2019;Cruz et al, 2021). C. bellicosus is an omnivorous species that induces bioturbation of sediments by mixing and resuspending the organic matter associated with the sediment, improving the bioavailability of trace metals (Andrade et al, 2020;Truchet et al, 2020), which are ingested and bioaccumulated in different tissues of this crab.…”
Section: Resultsmentioning
confidence: 99%
“…In the sediments, these trace metals become bioavailable, and bioaccumulation of metals in C. bellicosus could be related to the feeding habits of the species, the rates of absorption and depuration, the environmental conditions, the bioavailability of the metals, the fine texture of the sediments, CaCO 3 content, and organic matter content (Jerome and Chukwuka, 2016;Álvaro et al, 2016;Chuan et al, 2017;Genç and Yilmaz, 2017;Çoğun et al, 2017;Annabi et al, 2018;Baki et al, 2018;Durmus et al, 2018;Saber et al, 2018;Hao et al, 2019;Cruz et al, 2021). C. bellicosus is an omnivorous species that induces bioturbation of sediments by mixing and resuspending the organic matter associated with the sediment, improving the bioavailability of trace metals (Andrade et al, 2020;Truchet et al, 2020), which are ingested and bioaccumulated in different tissues of this crab.…”
Section: Resultsmentioning
confidence: 99%
“…The free carbohydrate and glycogen contents were assayed with the Anthrone method. Additionally to Andrade et al (2020), we assayed the free carbohydrates as suggested by Foray et al (2012). Briefly, we collected 150 μl of the initial supernatant of each insect sample into a microplate well and evaporated the well contents for 120 min at room temperature until a volume of approximately 10 μl was reached.…”
Section: Methodsmentioning
confidence: 99%
“…The insects were placed in phosphate buffer (300 and 600 μl for replicates below and above 500 μg, respectively), homogenised in a bead-beating tube for 1 min 30 s at 25 Hz, and centrifuged for 5 min at 500 g and 4°C. Protein and glycogen assays were realised according to Andrade et al (2020). The total protein content was assayed with the Bradford method (Bradford, 1976) using bovine serum albumin as a standard.…”
Section: Body Store Assaysmentioning
confidence: 99%
“…The amount of fine sediments stored in the 2 dam reservoirs was estimated as 1,800,000 m 3 (IDRA, 2012). A small part of the reservoir was contaminated with heavy metals (Andrade et al, 2020), but these sediments were dredged and safely stored outside the riverbed before the removal. The most upstream dam-Vezins Dam (36 m height)was removed in 2019 after 1 year of regular decrease of the water level in the reservoir, whereas the second dam-Roche-qui-Boit Dam (16 m height)-was completely removed in 2022 (see Dézerald et al, 2023 for details).…”
Section: Study Sitementioning
confidence: 99%